Evaluation of Survival Outcomes With Trimodal Therapy as Primary Therapy for Non-organ-confined Bladder Cancer - Guo, Yadong; Jie, Xiaoliang; Zhang, Aihong; Zhang, Wentao; Wang, Ruiliang; Zhang, Junfeng; Mao, Shiyu; Wu, Yuan; Wang, Longsheng; Zhang, Ziwei; Yan, Yang; Wang, Ping; et al. (Frontiers in Oncology, 2019)
Background: For patients with non-organ-confined bladder cancer (NOCBCa), radical cystectomy (RC) has demonstrated survival benefits. However, the relative survival benefit of trimodal therapy (TMT) is unclear. Methods: Patients diagnosed with NOCBCa (cT4bN0M0, cTxN1-3M0 or TxNxM1) were identified in the Surveillance, Epidemiology, and End Results (SEER) database (2004-2015). Patients were grouped based on their definitive treatment for bladder cancer (RC or TMT with maximal transurethral resection, chemotherapy, or radiotherapy). All-cause mortality (ACM) and bladder cancer-specific mortality (BCSM) were assessed by Cox proportional hazard regression and competitive risk models. Results: A total of 2,988 patients met the inclusion criteria and were treated with RC (83.5%) or TMT (16.5%). Patients who underwent TMT had higher 5-year ACM (91.3%) and BCSM (88.8%) results compared to patients who underwent RC (82.6% and 75.0%, respectively) (P < .001). Adjusted hazard rate (AHR) analysis showed that TMT was associated with higher ACM (AHR: 1.33, 95% CI: 1.15-1.54, P < .001) and higher BCSM (AHR: 1.32, 95% CI: 1.13-1.54, P = .001). Subgroup analysis revealed no differences between RC and TMT among patients aged ≥ 80 years, or between patients at stage T3-4, N2-3, or M0 (P > .05). Conclusions: Compared to TMT, RC was associated with a significant decrease in ACM and BCSM. Patients with age ≥ 80 years, T3-4, N2-3, or M0 showed no difference in prognosis between RC and TMT.